Medidas de adequação ambiental para um laticínio de pequeno porte com vista à implantação de um sistema de gestão ambiental - Veiga, Thaísa Gabriela (2018)
The environmental issue in industrial processes becomes more and more an essential requirement for the valorization of property and services, especially in an extremely competitive economic scenario. Furthermore, the connotation of these requirements with stricter environmental legislation promoted the development of environmental protection practices like, for example, water reuse, the treatment of residue generated in the production process and the establishment of Environmental Management System (EMS). However, many businesses, mainly those of small-scale, end up leaving preventive practices in the background, either due to lack of necessary structure for the establishment of more sustainable systems or for limited resources. In this context, the current study aims to propose measures of environmental development for a small-scale dairy farm located in the city of Toledo, Paraná. Therefore, an exploratory qualitative investigation was developed through bibliography survey, observation of the dairy farm LACTOMESA® and analysis of the documentation that govern the operation of a dairy farm and the legal suppositions of environmental protection. Through the observation of the productive process of the company, it was possible to pinpoint which aspects and environmental impacts involved in the dairy farm operation, among them: liquid effluent, atmospheric emissions, solid residue and noises. It allowed, later on, the evaluation of mitigating measures and possible environmental improvements for the dairy farm, in addition to the proposition of an adequate model of EMS for it. This way, it was possible to identify the steps of the productive process that require improvements or even the need for new implementations so that the dairy farm may develop its activities minimizing progressively the damage caused of its processes. Moreover, the analysis conducted in this study contribute so that other small-scale businesses may take the suggested measures as example and thus guarantee the environmental quality in their productive processes in the constructions of an EMS.